2016
DOI: 10.2147/dmso.s97036
|View full text |Cite
|
Sign up to set email alerts
|

Prescription omega-3 fatty acid products: considerations for patients with diabetes mellitus

Abstract: Type 2 diabetes mellitus (T2DM) and metabolic syndrome contribute to hypertriglyceridemia, which may increase residual risk of cardiovascular disease in patients with elevated triglyceride (TG) levels despite optimal low-density lipoprotein cholesterol (LDL-C) levels with statin therapy. Prescription products containing the long-chain omega-3 fatty acids (OM3FAs) eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) are an effective strategy for reducing TG levels. This article provides an overview of pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 64 publications
0
7
0
Order By: Relevance
“…Several mechanisms may explain the favourable associations between n -3 fatty acids and the risk of CVD. Previous clinical trials looking at intermediate cardiovascular outcomes among people with diabetes have reported that n -3 fatty acid supplementation could lower triacylglycerol concentrations [ 35 , 36 ], improve arterial blood flow and attenuate inflammatory signals [ 37 , 38 ]. These effects were supported by clinical trials in the general population and in experimental studies [ 39 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several mechanisms may explain the favourable associations between n -3 fatty acids and the risk of CVD. Previous clinical trials looking at intermediate cardiovascular outcomes among people with diabetes have reported that n -3 fatty acid supplementation could lower triacylglycerol concentrations [ 35 , 36 ], improve arterial blood flow and attenuate inflammatory signals [ 37 , 38 ]. These effects were supported by clinical trials in the general population and in experimental studies [ 39 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Evidence specifically pertinent to patients with diabetes is relatively sparse. Clinical trials looking at intermediate cardiovascular disease outcomes among adults with diabetes have consistently reported that marine n-3 supplements could lower triglyceride concentrations,45 improve arterial blood flow, and ameliorate inflammatory conditions that predispose cardiovascular disease events 4647 Meanwhile, a secondary analysis of the JELIS study found that eicosapentaenoic acid supplementation (1.8 g/day) for 4.6 years led to a 22% reduction in risk of coronary artery disease among 4565 adults with type 2 diabetes or impaired glucose metabolism,48 but this effect was not observed in another randomized controlled trial (0.9 g/day) with a larger sample size (n=12 536) and longer follow-up (6.2 years) 49.…”
Section: Discussionmentioning
confidence: 99%
“…Insulin sensitivity seems to increase after supplementation of n-3 PUFAs in relation to non-esterified fatty acid reduction [ 27 ]. EPA and DHA prescription for Type 2 diabetes mellitus significantly reduces the levels of triglyceride known to be responsible for fat accumulation, thereby reducing the risk of developing hypertriglyceridemia [ 28 ]. However, the EPA-only prescription seems slightly better as it does not increase the concentration of low-density lipoprotein cholesterol, decreases total cholesterol levels, and results in fewer gastrointestinal effects than DHA-only prescription [ 28 ].…”
Section: Polyunsaturated Fatty Acids and Human Healthmentioning
confidence: 99%
“…EPA and DHA prescription for Type 2 diabetes mellitus significantly reduces the levels of triglyceride known to be responsible for fat accumulation, thereby reducing the risk of developing hypertriglyceridemia [ 28 ]. However, the EPA-only prescription seems slightly better as it does not increase the concentration of low-density lipoprotein cholesterol, decreases total cholesterol levels, and results in fewer gastrointestinal effects than DHA-only prescription [ 28 ]. Interestingly, these n-3 PUFA-reinforced diets do not result in glucose metabolism impairment in diabetic patients, as shown in 14 clinical trials [ 29 ].…”
Section: Polyunsaturated Fatty Acids and Human Healthmentioning
confidence: 99%